Damage identification of structures based on sensitivity equations using PCA and PSD data. (June 2023) - Fallah, Narges; Hoseini Vaez, Seyed Rohollah; Esfandiari, Akbar
This article presents a novel model updating approach to the problem of structural damage identification. The approach is based on principal component analysis (PCA) of power spectral density (PSD) data obtained from incompletely measured structural responses. Damage detection was done by solving an innovative sensitivity equation based on least-squares optimization that could help solve the problem in a time-efficient manner and extend the results for industrial applications. Simulations of a 2D steel truss and a 2D steel frame were considered for a thorough comparison. The simulation results clearly showed the effectiveness of the method and its superior performance for solutions such as a PSD-only strategy and frequency response function (FRF) based data analysis along with singular value decomposition.